If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(1 + -5x) + 5(-8x + -2) = -4 + -8x (1 * -5 + -5x * -5) + 5(-8x + -2) = -4 + -8x (-5 + 25x) + 5(-8x + -2) = -4 + -8x Reorder the terms: -5 + 25x + 5(-2 + -8x) = -4 + -8x -5 + 25x + (-2 * 5 + -8x * 5) = -4 + -8x -5 + 25x + (-10 + -40x) = -4 + -8x Reorder the terms: -5 + -10 + 25x + -40x = -4 + -8x Combine like terms: -5 + -10 = -15 -15 + 25x + -40x = -4 + -8x Combine like terms: 25x + -40x = -15x -15 + -15x = -4 + -8x Solving -15 + -15x = -4 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -15 + -15x + 8x = -4 + -8x + 8x Combine like terms: -15x + 8x = -7x -15 + -7x = -4 + -8x + 8x Combine like terms: -8x + 8x = 0 -15 + -7x = -4 + 0 -15 + -7x = -4 Add '15' to each side of the equation. -15 + 15 + -7x = -4 + 15 Combine like terms: -15 + 15 = 0 0 + -7x = -4 + 15 -7x = -4 + 15 Combine like terms: -4 + 15 = 11 -7x = 11 Divide each side by '-7'. x = -1.571428571 Simplifying x = -1.571428571
| F(x)=5x^2+11x-12 | | -14k--19k-8k=-18 | | 4x^2-14x=2(2x^2-7x) | | 12x+5=17x-10 | | (x^2-4x+4)(x^2+9)= | | y-x^2= | | 4.5x-2=2.5x+8 | | s/19=150 | | 8b^5+20b^3+48H^4x^2=0 | | 14xd=154 | | 14k-19k-8k=18 | | 2(x-5)=4-7(7-x) | | -10-14b-3-(-5b)= | | 4a^2b^7+2ab^4-6ab^7= | | 8y-6x+7x= | | 7x-2(-10+5x)=11 | | 4+4y=95 | | 5x-11/3=43 | | -7(1-2m+n)= | | 2(x+5)=4-2(7+x) | | 2x+(x-5)=55 | | 15x^2y-35xy-20x= | | (9x-7)(5x+9)=0 | | 6y^2-10y+3=0 | | 17-(6x+3)= | | 12x^5-19x^3+11x^2= | | 35-5b=0 | | 7(x+4m+3)= | | -9b-1+18+4b= | | z-24=9 | | a=3600-0.8y | | 7(x-3)=4x+3(x-8) |